Genetic variations in estrogen and progesterone pathway genes in preeclampsia patients and controls in Bavaria - Pretscher, Jutta; Rübner, Matthias; Ekici, Arif Bülent; Rödl, Melanie; Hübner, Hanna; Schwitulla, Judith; Titzmann, Adriana; Hartwig, Charlotte; Beckmann, Matthias; Fasching, Peter; Schneider, Michael; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2020)
Purpose: Hypertensive pregnancy disorders and preeclampsia are major causes of maternal and fetal morbidity and mortality worldwide. Many different organs are involved in the diseases’ clinical phenotype. The underlying mechanism is still unknown, with a possible genetic component. This case–control study investigated effects on the risk of preeclampsia of genetic variations (single nucleotide polymorphisms, SNPs) in the estrogen and progesterone pathway genes. Methods: The study included 167 patients with preeclampsia and 115 healthy controls from the “Franconian Maternal Health Evaluation Studies” (FRAMES). All patients completed an epidemiological questionnaire, data from which were correlated with prospective data on pregnancy and labor. DNA was isolated from blood samples and genotyping was done by PCR. Variants in the aromatase gene CYP19A1 (rs10046, rs4646), progesterone receptor gene (rs1042838, rs10895068), and estrogen receptor-α gene (rs488133) were examined, and the genotype distribution in the two groups was analyzed statistically. Results: A significant difference in the distribution frequency of genotypes between preeclampsia patients and controls was identified in one of the five SNPs. For rs10895068 in the progesterone receptor gene, genotype G/A was significantly more frequent among cases than controls (P = 0.023). No significant differences between the two cohorts were found in the other SNPs. Conclusions: This study showed a significant association between only one SNP in the progesterone receptor and preeclampsia. Other studies have also noted genetic aspects of preeclampsia. The underlying mechanism and causal relationship are not yet known, and further research is needed to explain the extent of genetic variations and the causal relationship in preeclampsia.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Genetic marker; Preeclampsia; Pregnancy; Single nucleotide polymorphism (SNP)